Europe undivided democracy, leverage, and integration after communism - Vachudova, Milada Anna (Oxford University Press, 2005)
"Europe Undivided analyses the development of East European States post-1989 and their dynamic relationship with the EU. The author examines how the influence of an enlarging EU has created a convergence towards liberal democracy throughout the region, and provides insights into how the EU will function after enlargement."--Provided by publisher.